HOW AND WHEN ISLAMIC WORK ETHIC LEADS TO EMPLOYEE VOICE IN URBAN MUSLIM COMMUNITY?: THE ROLE OF CIVILITY CLIMATE AND ORGANIZATIONAL IDENTIFICATION - Suryani Suryani; Hendryadi Hendryadi; Itang Itang; Ali Akhmadi; Yulius Dharma; Swarmilah Hariani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2023)
The current study uncovers a new paradigm in studying employee voice using a religious approach: Islamic work ethics (IWE). The research model involves a direct relationship between IWE and employee voice, indirectly through civility climate, and a moderate effect of organizational identification in urban Muslim communities, especially in the education sector. A time-lag data-collecting method captured 278 lecturers at various Islamic universities. The PLS-SEM analysis results confirmed most hypotheses: first, the IWE positively relates to civility and employee voice. Second, the result demonstrated that civility climate plays a significant role in encouraging employee voice. However, the study did not find evidence to support civility climate's interplay role in the relationship between IWE and employee voice. Finally, the research confirmed that organizational identification is a crucial predictor and moderator of employee voice. The urban Muslim community is a diverse group, both culturally and ethnically. This diversity creates an environment that fosters positive cultural exchange and critical thought discussions regarding Islamic thought. The study's findings provide valuable insights into the relevance and implementation of IWE in urban Muslim communities, particularly in Indonesia's education sector. The proposed model has practical and theoretical implications for HR practitioners and the study of IWE in modern society and organizations.